PENERAPAN TEKNOLOGI TEPAT GUNA LEMARI PENGERING DAN MEJA POLA PADA UMKM ZULPAH BATIK DI TANJUNG BUMI - Laily, Nur; Baihaqy, Ahmad; Nurmianto, Eko; Satria, Vinza Hedi; Sari, Juwita (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
Zulpah Batik SME in Tanjung Bumi faces significant challenges during the rainy season, as batik drying relies on sunlight, taking up to 5 hours in clear weather, 2 days in overcast conditions, and halting entirely during prolonged rainfall. Additionally, creating batik patterns using large fabrics is hindered by the absence of an adequate workspace, as the SME has only utilized standard writing desks. To address these issues, a batik drying cabinet powered by LPG and an ergonomic batik design table equipped with LED lighting were introduced. The drying cabinet reduces drying time to just 1 hour regardless of weather, with a controlled temperature of 70 ± 5°C, enabling continuous production. Meanwhile, the ergonomic design table, with adjustable height (76 cm standard) and dimensions of 122 cm x 200 cm, enhances pattern-making efficiency and precision. These appropriate technology solutions significantly improve production efficiency and quality, ensuring uninterrupted operations during the rainy season and facilitating better batik pattern creation. Keywords: Drying Cabinet, Pattern Table, Appropriate Technology, Batik